Bacterial Biofilm in Salivary Gland Stones: Cause or Consequence?. (12th January 2016) - Fusconi, Massimo; Petrozza, Vincenzo; Schippa, Serena; de Vincentiis, Marco; Familiari, Giuseppe; Pantanella, Fabrizio; Cirenza, Mirko; Iebba, Valerio; Battaglione, Ezio; Greco, Antonio; Gallipoli, Camilla; Campo, Flaminia; et al.
Abstract : Objective: The pathogenesis of salivary calculi is not yet clear; however, 2 theories have been formulated: (1) "the classic theory, " based on calcium microdeposits in serous and ductal acinous cells, successively discharged into the ducts; (2) "the retrograde theory, " based on a retrograde migration of food, bacteria, and so on from the oral cavity to the salivary duct. The aim of the present study is to highlight the role of bacteria and biofilm in stone formation. Study Design: Case series without comparison. Setting: Laboratory of the Department of Anatomical Pathology. Subjects and Methods: Traditional optic microscopy and scanning electron microscopy were carried out on 15 salivary gland calculi that were collected from 12 patients. A qPCR (quantitative real‐time polymerase chain reaction) assay was performed to highlight the presence of bacterial DNA on each stone. Results: Optic microscopy showed formations that—due to their size, shape, and Gram and Giemsa staining—seemed to be Gram‐positive bacterial cells. PAS‐ (periodic acid–Schiff) and alcian‐PAS‐positive staining matrix was present around them. The ultrastructural observation of the material processed for scanning electron microscopy showed the presence of structures resembling bacterial cells in the middle of the stones, surrounded by soft, amorphous material. Results of qPCR showed the presence of bacterial DNA in the internal part of the tissue sample. Conclusions: The presence of bacteria and/or bacterial products resembling biofilm in salivary gland stones supports the "retrograde theory." This evidence may support the hypothesis that biofilm could be the causative effect of lithiasic formations.